Fabrication of photo-enzyme coupled catalysts with the desired electron transport channel for the high-efficiency synergic degradation of bisphenol A in water. Issue 36 (30th August 2022) - Ma, Xinnan; Wu, Jiacong; Han, Juan; Wang, Lei; Li, Chunmei; Wang, Yun
Abstract : Ingenious design of electron transport channels is crucial to improving the electron utilization efficiency in novel photo-enzyme coupled catalyst systems. Abstract : Ingenious design of electron transport channels is crucial to improving the electron utilization efficiency in novel photo-enzyme coupled catalyst systems. Herein, carbon nanotubes (CNT) were used as a bridge between CN and HRP for the electron transformation in the HRP/CNT/CN photo-enzyme system for the first time, which improved the separation efficiency of photogenerated charge carriers due to its unique advantage. Besides, the steric hindrance of CNT can effectively limit the damage of superoxide radicals toward HRP and increase the service life of HRP, which effects the enhancement of stability for HRP. Thus, the desired high-efficiency and stable degradation of the target BPA in water was achieved. These findings may provide a new idea for the design of a photo-enzyme coupled system with an oriented electron transport channel in a controllable manner.